ENERGETIC SECURITY PARAMETERS OF BIOLOGICAL TRANSILYUMINATSIYI OF NANOSYSTEMS EYE - Запорожець, А.; Плюто, І.; Замурняк, О.; Тяжка, Н.; Панасенко, Г.; Тіницька, Я. (Science-based technologies, 2011)
The article considers the method ofgetting the fundus image in real time in the reflected visible and nearinfrared wavelengths. There was made the theoretical calculations of exposure’sallowable maximum levelwith collimated laser radiation for eyes and skin in the range from 400 to 1400 nm.